Reassessing velocity generation in hammer throwing - Maheras, A. V. (New Studies in Athletics, 2009)
In the hammer throw, the exertion of the force necessary to increase the horizontal velocity of the implement is thought to take place mainly when both the thrower's feet are in contact with the ground during the double-support phases of the turns. Coaches have therefore sought to maximise the duration and the effectiveness of the double-support phases while minimising the length of the single-support phases, when it is assumed that the thrower is preparing for the next double-support. However, as scientific understanding of the event has developed things have become less clear. It is now known that the horizontal velocity of the hammer is increased mainly in the winds or early part of the throw, when the thrower is stationary or rotating slowly, and that the observed increase in velocity during the turns is due not to a horizontal pull-push of the feet against the ground but to the addition of vertical velocity and a shortening of the hammer radius. Therefore, emphasis on the double-support phases may well be misplaced. Stressing that there is still much that is not known about the hammer throw, the author explains current understanding of the event in detail and makes recommendations for coaches to consider.